Memory in Times of War (2009)
This article describes the complexity of transitional justice in Colombia since the approval of Law 975, known as the “Justice and Peace Law,” and the demobilization of the United Autodefenses of Colombia in 2005. In the middle of the open war between the Revolutionary Armed Forces of Colombia and the Colombian government, different victims' organizations have empowered themselves around their struggle to reconstruct memory.